2008
DOI: 10.1111/j.1369-7625.2007.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

‘I do not need to… I do not want to… I do not give it priority…’– why women choose not to attend cervical cancer screening

Abstract: Objective To describe and interpret why women with no cervical smear taken during the previous 5 years choose not to attend a cervical cancer screening (CCS) programme.Background CCS programme is a service for early detection of cervical cancer. Today, some women choose not to attend the programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 31 publications
6
56
1
4
Order By: Relevance
“…9,[13][14][15] In addition, the health professionals suggested that population mobility, particularly in young women, might be a problem, and some thought that structural factors such as GP incentivisation and the change in the age of first screening might contribute to declining participation in this group; barriers that women themselves would not necessarily be aware of. For some women, the decision not to attend screening was informed; they perceived that the costs outweighed the benefits or they were not sexually active.…”
Section: Discussionmentioning
confidence: 99%
“…9,[13][14][15] In addition, the health professionals suggested that population mobility, particularly in young women, might be a problem, and some thought that structural factors such as GP incentivisation and the change in the age of first screening might contribute to declining participation in this group; barriers that women themselves would not necessarily be aware of. For some women, the decision not to attend screening was informed; they perceived that the costs outweighed the benefits or they were not sexually active.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have described identifying non-attendeers from health records held by service providers and contacting the individuals directly by phone or letter to invite them to participate (Hall et al, 2015; McCaffery et al, 2001; Oscarsson, Mijma, & Benzein, 2008). Other studies have described forging links with community leaders to access their networks and approach individuals directly (Quaife, Marlow, McEwen, Janes, & Wardle, 2016) or have offered financial incentives to encourage participation (Ellis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they may be relatively unaware of the fact that the earlier stages of cancer can be asymptomatic. Symptoms clearly influence perceived risk, with lack of symptoms being a frequent explanation for the lack of need for screening (Oscarsson, Wijma, & Benzein, 2008) even though asymptomatic disease is the screening target. Individual characteristics seem also to inform perception of personal risk, including sociodemographic, health, and lifestyle factors (e.g.…”
Section: Individual Determinants Of Cancer Screening Participationmentioning
confidence: 99%